Moving through language: a behavioural and linguistic analysis of spatial mental model construction - Parente, Fabio (2016)
Over the past few decades, our understanding of the cognitive processes underpinning our navigational abilities has expanded considerably. Models have been constructed that attempt to explain various key aspects of our wayfinding abilities, from the selection of salient features in environments to the processes involved in updating our position with respect to those features during movement. However, there remain several key open questions. Much of the research in spatial cognition has investigated visuospatial performance on the basis of sensory input (predominantly vision, but also sound, hapsis, and kinaesthesia), and while language production has been the subject of extensive research in psycholinguistics and cognitive linguistics, many aspects of language encoding remain unexplored. The research presented in this thesis aimed to explore outstanding issues in spatial language processing, tying together conceptual ends from different fields that have the potential to greatly inform each other, but focused specifically on how landmark information and spatial reference frames are encoded in mental representations characterised by different spatial reference frames. The first five experiments introduce a paradigm in which subjects encode skeletal route descriptions containing egocentric (“left/right”) or allocentric (cardinal) relational terms, while they also intentionally maintain an imagined egocentric or allocentric viewpoint. By testing participants’ spatial knowledge either in an allocentric (Experiments 1-3) or in an egocentric task (Experiments 4 and 5) this research exploits the facilitation produced by encoding-test congruence to clarify the contribution of mental imagery during spatial language processing and spatial tasks. Additionally, Experiments 1-3 adopted an eye-tracking methodology to study the allocation of attention to landmarks in descriptions and sketch maps as a function of linguistic reference frame and imagined perspective, while also recording subjective self-reports of participants’ phenomenal experiences. Key findings include evidence that egocentric and allocentric relational terms may not map directly onto egocentric and allocentric imagined perspectives, calling into question a common assumptions of psycholinguistic studies of spatial language. A novel way to establish experimental control over mental representations is presented, together with evidence that specific eye gaze patterns on landmark words or landmark regions of maps can be diagnostic of different imagined spatial perspectives. Experiments 4 and 5 adopted the same key manipulations to the study of spatial updating and bearing estimation following encoding of short, aurally-presented route descriptions. By employing two different response modes in this triangle completion task, Experiments 4 and 5 attempted to address key issues of experimental control that may have caused the conflicting results found in the literature on spatial updating during mental navigation and visuospatial imagery. The impact of encoding manipulations and of differences in response modality on embodiment and task performance were explored. Experiments 6-8 subsequently attempted to determine the developmental trajectory for the ability to discriminate between navigationally salient and non-salient landmarks, and to translate spatial relations between different reference frames. In these developmental studies, children and young adolescents were presented with videos portraying journeys through virtual environments from an egocentric perspective, and tested their ability to translate the resulting representations in order to perform allocentric spatial tasks. No clear facilitation effect of decision-point landmarks was observed or any strong indication that salient navigational features are more strongly represented in memory within the age range we tested (four to 11 years of age). Possible reasons for this are discussed in light of the relevant literature and methodological differences. Globally, the results presented indicate a functional role of imagery during language processing, pointing to the importance of introspection and accurate task analyses when interpreting behavioural results. Additionally, the study of implicit measures of attention such as eye tracking measures has the potential to improve our understanding mental representations, and of how they mediate between perception, action, and language. Lastly, these results also suggest that synergy between seemingly distinct research areas may be key in better characterising the nature of mental imagery in its different forms, and that the phenomenology of imagery content will be an essential part of this and future research.